2014
DOI: 10.3389/fnana.2014.00068
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-9 involvement in the structural plasticity of dendritic spines

Abstract: Dendritic spines are the locus for excitatory synaptic transmission in the brain and thus play a major role in neuronal plasticity. The ability to alter synaptic connections includes volumetric changes in dendritic spines that are driven by scaffolds created by the extracellular matrix (ECM). Here, we review the effects of the proteolytic activity of ECM proteases in physiological and pathological structural plasticity. We use matrix metalloproteinase-9 (MMP-9) as an example of an ECM modifier that has recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 199 publications
(263 reference statements)
1
53
0
Order By: Relevance
“…Also TAS was significantly correlated with PANSS negative score and total psychopathological score which is in contrast to a previous study where they found weak correlation between TAS and PANSS positive score [17]. Even though the mechanism through which MMP-9 is involved in the pathogenesis of schizophrenia is unclear, we speculated that elevated MMP-9 level due to oxidative stress may cause elongation and thinning of dendritic spines which alters the synaptic transmission in the brain leading to aberrant synaptic plasticity [33].…”
Section: Discussionmentioning
confidence: 76%
“…Also TAS was significantly correlated with PANSS negative score and total psychopathological score which is in contrast to a previous study where they found weak correlation between TAS and PANSS positive score [17]. Even though the mechanism through which MMP-9 is involved in the pathogenesis of schizophrenia is unclear, we speculated that elevated MMP-9 level due to oxidative stress may cause elongation and thinning of dendritic spines which alters the synaptic transmission in the brain leading to aberrant synaptic plasticity [33].…”
Section: Discussionmentioning
confidence: 76%
“…Components of the ECM, including matrix metalloproteinases (MMPs), have been proposed to actively contribute to dendritic spine remodeling. Accumulating evidence suggests a specific role for MMP-9 in regulating the structural plasticity of dendritic spines [4]. …”
Section: Introductionmentioning
confidence: 99%
“…MMPs are the family of zinc-dependent endopeptidases that degrade ECM proteins and are permissive to a number of events classically associated with synaptic plasticity, including morphologic changes in dendritic spines (Michaluk et al, 2011;Stawarski et al, 2014;Verslegers et al, 2015), NMDAR lateral diffusion, and AMPAR phosphorylation and insertion (Michaluk et al, 2009;Szepesi et al, 2014). Specifically, MMP-2 and MMP-9 play important roles in aberrant synaptic plasticity associated with neurologic disorders (Mizoguchi et al, 2011;Stawarski et al, 2014), with recent research demonstrating the importance of MMPs in drug behavioral effects and relapse. For example, inhibiting MMP-9 attenuates cocaine CPP (Brown et al, 2008), and MMP-9 is involved in regulating synaptic plasticity underlying acquisition of nicotine CPP (Natarajan et al, 2013).…”
Section: Extracellular Matrixmentioning
confidence: 99%